Synthesis and biological evaluation of (3/4-(pyrimidin-2-ylamino)benzoyl)-based hydrazine-1-carboxamide/carbothioamide derivatives as novel RXRα antagonists. (1st January 2020) - Qin, Jingbo; Liu, Jie; Wu, Chunxiao; Xu, Jianwen; Tang, Bowen; Guo, Kaiqiang; Chen, Xiaohui; Liu, Weihao; Wu, Tong; Zhou, Hu; Fang, Meijuan; Wu, Zhen
Abstract: Abnormal alterations in the expression and biological function of retinoid X receptor alpha (RXRα) have a key role in the development of cancer. Potential modulators of RXRα as anticancer agents are explored in growing numbers of studies. A series of (4/3-(pyrimidin-2-ylamino)benzoyl)hydrazine-1-carboxamide/carbothioamide derivatives are synthesised and evaluated for anticancer activity as RXRα antagonists in this study. Among all synthesised compounds, 6A shows strong antagonist activity (half maximal effective concentration (EC50 ) = 1.68 ± 0.22 µM), potent anti-proliferative activity against human cancer cell lines HepG2 and A549 cells (50% inhibition of cell viability (IC50 ) values < 10 µM), and low cytotoxic property in normal cells such as LO2 and MRC-5 cells (IC50 values > 100 µM). Further bioassays indicate that 6A inhibits 9-cis-RA-induced activity in a dose-dependent manner, and selectively binds to RXRα-=LΒD with submicromolar affinity (Kd = 1.20 × 10 −7 M). 6A induces time-and dose-dependent cleavage of poly ADP-ribose polymerase, and significantly stimulates caspase-3 activity, leading to RXRα-dependent apoptosis. Finally, molecular docking studies predict the binding modes for RXRα-LBD and 6A . Graphic Abstract: Compound 6A with low cytotoxic property in normal cells acts as a selective RXR alpha ligand to promote TNF alpha-mediated apoptosis of cancer cells. UF0001